(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2023)
This study looks at the changing environment of media freedom in Pakistan between August 2018 and April 2022, under the populist governments of Imran Khan and Pervez Musharraf. The research uses the gatekeeping theory as a framework to examine the state of media freedom while acknowledging the revolutionary effects of digital technology on communication. Media networks were founded on the fundamental idea that people should produce, assess, and disseminate information; this idea emphasized the media’s initial function as a medium of communication, as opposed to a means of influencing behavior and social standards. This research, which is qualitative, includes semi-structured interviews with twelve senior journalists from leading Pakistani newspapers and television networks. These individuals shared their ideas, opinions, and feelings about media freedom based on their combined more than ten years of experience in the field. This research, which is qualitative, includes semi-structured interviews with twelve senior journalists from leading Pakistani newspapers and television networks. These individuals shared their ideas, opinions, and feelings about media freedom based on their combined more than ten years of experience in the field.